(untitled) (Fiep Bulletin - online, 2021)
Considering the importance of dance, it makes possible the charm and magic of feeling the movements of dominating your rhythm, feeling the emotions and feelings in the choreography and in free dance. The goal is to know the quality of life of the needy intellectuals who practice dance. The population and sample of the referred study are dance practitioners from APAE, Campina Grande - Pb, whose analysis will be performed by their caregivers, who will answer the Quality of Life questionnaire. This is a descriptive and exploratory study, which aims to identify the quality of life of the needy intellectuals who practice dance. The statistical procedures will be performed using the Microsoft Excel for Windows 10 program, and presented in the form of tables and graphs, by means and standard deviations.